Adverse fetal and neonatal outcomes in pregnancies with confirmed Zika Virus infection in Rio de Janeiro, Brazil: A cohort study. - Juliana P Souza; Maria Dalva B B Méio; Laura Medeiros de Andrade; Mirza R Figueiredo; Saint Clair Gomes Junior; Jose Paulo Pereira Junior; Elizabeth Brickley; Maria Elisabeth Lopes Moreira (Public Library of Science (PLoS), 2021)
Objective To analyze adverse fetal and neonatal outcomes of Zika virus infection by the timing of infection during pregnancy. Method: Cohort study of 190 pregnancies with 193 offspring with a positive RT-PCR test for Zika virus (March/2016 to April/2017). Results Death or defects related to congenital Zika virus infection were identified in 37.3% of fetuses and newborns, and microcephaly in 21.4% of the newborns. The proportion of small for gestational age newborns was 21.9%. Maternal symptoms in the first trimester were significantly associated with the birth of newborns with microcephaly/cerebral atrophy, small for gestational age and with the deaths (one abortion, one stillbirth and the two neonatal deaths). Maternal infection during the second trimester was further associated with asymptomatic newborns at birth. The study showed that 58.5% of the offspring with microcephaly and / or cortical atrophy were small for gestational age, with an evident decrease in symptomatic offspring without microcephaly, 24.1%, and with only 9.1% in the asymptomatic group. Conclusion This study showed that the earlier the symptoms appear during gestation, the more severe the endpoints. We found a higher percentage of small for gestational age newborns exposed to Zika virus early in gestation. We also found a group of apparently asymptomatic newborns with proven Zika infection, which highlights the importance of follow up studies in this population.